Identifikasi Bahaya Proses Blasting dan Painting di Perusahaan Fabrikasi Menggunakan Job Hazard Analysis (JHA) - Arina 'arofatuz Zakiyah; Denny Ardyanto; Mohammad Zainal Fatah; Meirina Ernawati (Yayasan Literasi Sains Indonesia, 2024)
The risk of accidents and occupational diseases is difficult to avoid, one of which is in fabrication companies because workers are in direct contact with objects and heavy equipment during work. One of the work areas that is at high risk of accidents and occupational diseases is the blasting and painting area. The objectives of this study are: (1) to identify potential hazards and possible risks (2) to control the risks of each process activity to ensure that the work is in a safe condition. The research method used is a qualitative descriptive approach method with risk analysis using job hazard analysis. The results of the study identified 52 potential hazards and risks with 9 types of hazards, namely psychological hazards, mechanical hazards, electrical hazards, fire hazards, blasting hazards, physical hazards, chemical hazards, biological hazards, and ergonomic hazards derived from 7 classifications of processes or work stages in the blasting and painting work area. Prevention and control efforts are carried out to reduce the risk as a whole by using a hierarchy of control.